Myosins A Superfamily of Molecular Motors - Coluccio, Lynne M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Few would have predicted 20 years ago that myosins constitute a superfamily with at least two-dozen classes and that these molecular motors are involved in a multitude of intracellular activities including cell division, cell movement, intracellular transport and signal transduction. Application of state-of-the-art cellular and molecular biological, structural biological, genetic, biochemical and biophysical techniques has provided and continues to provide critical information regarding the structure–function relationship; and the cellular roles of various myosins in organisms as diverse as protozoa, yeast, plants and higher animals. The association of myosins with diseases including neurological disorders, immu- deficiencies, cardiomyopathies, hearing and vision loss testify to the importance of understanding the biochemical properties and cellular roles of myosins. The 16 chapters in this volume summarize the tremendous progress made in studying members of the myosin superfamily in recent years and offer critical insight into what future research will yield. I would like to express my sincere gratitude to the authors of this volume. It was a pleasure to work with each of you and I thank you for the considerable efforts in making this international endeavor possible. I also thank John Trinick from the University of Leeds, UK, for the elegant montage of images of single molecules of myosins on the cover, which beautifully shows the structures of some of these amazing molecules. The able assistance of Marlies Vlot from Springer and Indumadhi Srinivasan from Integra Software Services for production of the book is greatly appreciated.
The Structural And Functional Diversity Of The Myosin Family Of Actin-Based Molecular Motors -- Myosin Structure -- The Myosin Family: Biochemical And Kinetic Properties -- Myosin I -- Myosin Ii: Sarcomeric Myosins, The Motors Of Contraction In Cardiac And Skeletal Muscles -- Smooth-Muscle Myosin II -- Non-Muscle Myosin II -- Class III Myosins -- Myosin V -- Myosin VI: A Multifunctional Motor Protein -- Myosin VII -- Plant Myosins VIII, XI, And XIII -- Class Ix Myosins -- Myosin X -- Myosin Class XIV And Other Myosins In Protists -- Myosin XVA.
Keywords: Cell biology; Biochemistry; Medicine; Cell Biology; Biochemistry, general; Biomedicine, general